Determinants of Bank Credit in Emerging Market Economies - Stepanyan, Vahram (IMF Working Papers; Working Paper ;, 2011)
We examine changes in bank credit across a wide range of emerging market economies during the last decade. The rich time-series and cross-section information allows us to draw broader lessons compared to many existing researches, which focus on a specific set of emerging market economies or on shorter time periods. Our results show that domestic and foreign funding contribute positively and symmetrically to credit growth. The results also indicate that stronger economic growth leads to higher credit growth, and high inflation, while increasing nominal credit, is detrimental to real credit growth. We also find that loose monetary conditions, either domestic or global, result in more credit, and that the health of the banking sector also matters. Finally, we discuss some policy lessons.